A decision support system for selecting sustainable materials in construction projects - Rashid Minhas, M.; Potdar, Vidyasagar; Ameri Sianaki, O. (2018)
© 2018 IEEE. Major construction activity has had a significant effect on the environment, the economy and society in the twenty first century. The gap between the energy required to supply such construction, and the actual energy produced, particularly in the building sector, has put enormous pressure on the selection of sustainable construction materials. Even though the construction industry continues to place this pressure on natural resources, it has also resulted in an increase in the production of waste material, which is being dumped all over the world. In recent years, a lot of work has been undertaken to develop sustainable buildings/housing. The selection of appropriate sustainable building materials is one of the most important processes in the building design and construction process. Immediate efforts are needed to improve the awareness of sustainable materials among decision makers as there is limited technological support to assist technical experts (i.e. engineers, estimators, architects, draftsmen etc.) in the decision-making process when searching for and selecting new sustainable construction materials and practices for different building components (e.g. walls, roof, slab etc.). Moreover, cyber-physical infrastructure and information technologies are essential to support the sustainability of construction projects; this will be discussed further in this paper.